Short Communication: Phytochemistry and chemical fingerprint of katuk (Sauropus androgynus) leaves extract from four varieties - FACHRUDDIN FACHRUDDIN; AGIK SUPRAYOGI; NOVRIYANDI HANIF (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Fachruddin, Suprayogi A, Hanif N. 2025. Short Communication: Phytochemistry and chemical fingerprint of katuk (Sauropus androgynus) leaves extract from four varieties. Biodiversitas 26: 824-830. Katuk (Sauropus androgynus) is a medicinal plant known to consist of four varieties based on the presence and distribution of white spots on the leaf surface. These characteristic differences affect the content of active compounds and their biological activities. This study aimed to determine the phytochemical content of crude ethanol extracts and to analyze the chemical fingerprints of the n-hexane fractions from the leaves of four S. androgynus varieties. The extraction process was conducted using ethanol to obtain the crude extract, followed by partitioning with n-hexane to separate the non-polar fractions. Qualitative phytochemical tests were performed on the crude ethanol extract, while chemical fingerprint analysis was carried out on the n-hexane fraction using LC-MS instruments. The results showed that the crude ethanol extract contained flavonoids, saponins, tannins, and steroids. LC-MS analysis revealed that all S. androgynus varieties shared similarities in their chemical fingerprint patterns, particularly the Zanzibar-Bastar varieties (six peaks on the chromatogram had the same retention times). The major compound groups found in the n-hexane fractions included triterpenoid glycosides (Zanzibar), diterpenoids (Bastar and Paris), and steroids (Kebo). These similar fingerprints and slight variations in chemical composition provide insights that are likely to produce subtly different pharmacological effects, thereby sparking further intrigue and eagerness for future research in the field of medicinal plant studies.